Quality Translation Evaluation: Understanding the Roles of Human Translation and Machine Translation - Dinul Qoyyimah, Nadiya; Nasution, Sahraini Yamni Nurul Falah; Repelita Waty Kembaren, Farida (PT. Kreasi Karya Majakata, 2023)
This paper explores the critical aspect of translation quality evaluation by examining the distinctive contributions of both human translation and machine translation. In an era where technology plays an ever-increasing role in translation processes, it is essential to comprehend the strengths and limitations of both human and machine translators. Through a comprehensive analysis of real-world translation examples and case studies, this research sheds light on the nuances of translation quality, emphasizing the interplay between human expertise and machine efficiency. By offering insights into the evaluation methodologies, criteria, and challenges associated with assessing translation quality, this study provides a valuable resource for professionals, researchers, and stakeholders seeking to enhance their understanding of the complex dynamics in the field of translation.